Reading childishly? Learning to read modernism: reading the child reader in modernism and psychoanalysis. Issue 7 (10th November 2017) - Tyson, Helen
ABSTRACT: This article focuses on portraits of childhood reading in writings by Sigmund Freud, Virginia Woolf and Marcel Proust. The figure of the child reader, I suggest, functions as one of what Charles Altieri has described as the 'projected readers' of modernism – the 'ideal' readers imagined in and constructed by modernist texts, as a way of modelling how we might respond imaginatively and psychologically to this difficult form of writing. But there is, of course, a fundamental disavowal at work in such representations of the child reader in works that are evidently not written for children to read. We, as adult readers, are solicited to identify as a child. What happens, I ask, when we do so? What is it that we are we being encouraged to identify with? Tracing the figure of the child reader through debates about difficulty, high and low culture, maturity and infantilism, in criticism and psychoanalysis, I suggest that this child reader is, crucially, an overdetermined figure. Modernism reminds us of a vestigial child in us all, but this is not an exclusionary regression imposed upon an implicitly inadequate reader by the highbrow text. Neither is this simply a fantasy of naïve consolation (the child as pure identification). The child reader, I argue, opens up the vexed psychic life of reading modernism.